2000
DOI: 10.1074/jbc.275.18.13420
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AT1 Receptor Internalization by Concanavalin A Blocks Angiotensin II-induced ERK Activation in Vascular Smooth Muscle Cells

Abstract: Angiotensin II (Ang II), 1 a major effector peptide of the renin-angiotensin system, is believed to play a critical role in the pathogenesis of cardiovascular remodeling associated with hypertension, heart failure, and atherosclerosis (1). Ang II binds to at least two types of receptor with high affinity, designated AT 1 and AT 2 receptors (2). We and others (3, 4) previously cloned the AT 1 receptor that belongs to the superfamily of heterotrimeric G protein-coupled receptors (GPCRs). The AT 1 receptor activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…Transactivation of EGFR has been implicated as a downstream mediator of PYK2 activation in angiotensin II-stimulated vascular smooth muscle cell hypertrophy (21,24,25,32). However, we found that direct activation of EGFR by binding of EGF did not stimulate Ca 2ϩ spiking despite activation of ERK1/2.…”
Section: Pyk2 and Ca 2ϩ Spiking In A7r5 Cellscontrasting
confidence: 53%
“…Transactivation of EGFR has been implicated as a downstream mediator of PYK2 activation in angiotensin II-stimulated vascular smooth muscle cell hypertrophy (21,24,25,32). However, we found that direct activation of EGFR by binding of EGF did not stimulate Ca 2ϩ spiking despite activation of ERK1/2.…”
Section: Pyk2 and Ca 2ϩ Spiking In A7r5 Cellscontrasting
confidence: 53%
“…3B, where the intracellular pool of CaR present at steady-state is no longer as prevalent, as well as in its ability to block EGF receptor-mediated ERK1/2 activation on the same blot (Fig. 3A), as the ability of concanavalin A to block the tyrosine kinase receptor-mediated activation of ERK1/2 has been demonstrated in some systems (33,36). These findings suggest that CaR internalization is partially required for ERK1/2 activation and further suggest the possibility that like other GPCRs, CaR activation of ERK1/2 by NPS R-467/ CaCl 2 and the later wave of 4 mM Ca 2ϩ activation may involve receptor cross-talk with the receptor-tyrosine kinase signaling pathway.…”
Section: Lack Of Erk1/2 Desensitization In Hek-hcar Cells With the Npmentioning
confidence: 99%
“…EGF receptor-mediated ERK1/2 activation (25 ng EGF/ml for 5 min) was used as a positive control to demonstrate that the concanavalin A was able to block this signaling pathway of this tyrosine kinase receptor pathway as previously demonstrated (33).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, receptor internalization appears to be dierentially regulated since upon AR stimulation and EGFR transactivation the b 2 subtype is internalized together with the EGFR while the a 2A AR remains on the surface of transfected COS-7 cells . Remarkably, concanavalin A (ConA)-treatment of vascular smooth muscle cells blocked AT 1 R internalization, AngII-induced EGFR transactivation and MAP kinase activation demonstrating the necessity of an intact cytoskeleton for receptor downregulation and signal transmission (Tang et al, 2000).…”
Section: Role Of Endocytosis In Signaling Of the Gpcr-transactivated mentioning
confidence: 99%